The Effect of Caulerpa Cylindracea Extract on Histopathology Depiction of Male Rattus Norvegicus Gaster Mucosa Induced by Indomethacin - FITRI HANDAJANI; Adya Hidayatullah; Nita Pranitasari (UNUSA Press, 2021)
ABSTRACT Background: A lot of food can repair gastric mucosal damage. For example, sea grapes or the Caulerpa cylindracea with its flavonoid content. Anti-inflammatory and anti-ulcer effect can reduce gastric lesions due to ulcerogenic agents. Indomethacin is used to induce gastric ulcers in experimental animals. Based on this background, this study was conducted to analyze the effect of Caulerpa cylindracea extract, on the histopathological picture of gastric mucosal damage of Rattus norvegicus male rats. Method: 32 male Rattus norvegicus rats were divided into 4 groups, (1) Group K(-), the untreated group, (2) Group K(+) induced by indomethacin 30mg/kgBB per head (3) Group P1 induced by indomethacin 30 mg/kgBB and Caulerpa cylindracea extract 1gr/100grBB per head, (4) Group P2, induced by indometacin 30mg/kgBB and 2gr/100grBB of Caulerpa cylindracea extract per head. Result: There was a significant difference (p = 0.001) between the degree of gastric mucosal damage in group K(+) given only indomethacin and group P1 given Indomethacin and 1gr/100grBB Caulerpa cylindracea extract. There was a significant difference (p = 0.001) between group K(+) and group P2 that given Indomethacin and 2g/100grBB Caulerpa cylindracea extract. There was a significant difference (p = 0.004) between group P1 and group P2. Data revealed on group K(-) without any treatment did not obtain significant results (p = 0.060) with group P2. Conclusion: Giving Caulerpa cylindracea extract with 1 gr/100grBB dose and 2gr/100grBB dose can repair mucosal damage in Rattus norvegicus male rats induced by indomethacin.